PENERAPAN MANAJEMEN BERBASIS SEKOLAH SMK NEGERI DAN SMK SWASTA SE-KARASIDENAN SEMARANG - Ikhsan, Sukardi; Anisykurlillah, Indah (Dinamika Pendidikan, 2010)
The objectives of this study are to analyze the implementation of School-Based Management in State and Private Vocational Schools (SMK) in Semarang Residence, and to identify the overall performance of State and Private Vocational Schools (SMK) in Semarang Residence which based on School-Based Management. The population of this study was all State and Private Vocational Schools (SMK) in Semarang Residence. The sample consisted of 10 State Vocational Schools (SMK) And 10 Private Vocational Schools (SMK). The results showed that either the principals of State Vocatinal Schools (SMK) or the principals of Private Vocational Schools (SMK) had very ideal criteria, curriculum and teaching programs had optimal criteria, staff had ideal criteria, students had ideal criteria and the infrastructure had highly optimized criteria.